ASISTENSI MENGAJAR: PENERAPAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION DALAM PEMBELAJARAN MATEMATIKA DI SMP NEGERI 49 MALUKU TENGAH - Pattimukay, Nessy (PAKEM : Jurnal Pengabdian Kepada Masyarakat, 2023)
Community Service activities are carried out to improve students’ abilities after applying the Realistic Mathematics Education learning approach at SMP Negeri Maluku Tengah. Subject in this activity were 18 students. The average student pretest results 29,1. These results have increased in the average posttest score which reached 61,94. This means that there is an increase in the score of the prestest to the posttest by 52,9 %. Futhermore, students response to learning that has been carried out by applying the Realistic Mathematics Education approach based on evaluation questionnaires, namely that most students give positive responses and hope that this avtivity will be carried out again in the following years